2017
DOI: 10.1186/s13569-017-0074-6
|View full text |Cite
|
Sign up to set email alerts
|

IDH1 or -2 mutations do not predict outcome and do not cause loss of 5-hydroxymethylcytosine or altered histone modifications in central chondrosarcomas

Abstract: BackgroundMutations in isocitrate dehydrogenase (IDH)1 or -2 are found in ~50% of conventional central chondrosarcomas and in up to 87% of their assumed benign precursors enchondromas. The mutant enzyme acquires the activity to convert α-ketoglutarate into the oncometabolite d-2-hydroxyglutarate (d-2-HG), which competitively inhibits α-ketoglutarate dependent enzymes such as histone- and DNA demethylases.MethodsWe therefore evaluated the effect of IDH1 or -2 mutations on histone modifications (H3K4me3, H3K9me3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
64
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 54 publications
(70 citation statements)
references
References 59 publications
(106 reference statements)
5
64
1
Order By: Relevance
“…Thus, increased levels of d ‐2‐HG have been found in cartilage tumors with an IDH mutation, and are able to competitively inhibit α‐KG dependent histone demethylases, affecting trimethylation of the H3K27 as well as H3K4. However, no difference in levels of H3K27 and H3K4 trimethylation was observed between IDH mutant and IDH wildtype CSs. Additionally, previous studies and sequencing performed in the lab showed that CH2879 harbors IDH1/2 wild‐type, JJ012 IDH1‐mutant (p.Arg132Gly), and SW1353 IDH2‐mutant (p.Arg172Ser), while the current study show effective induction of apoptosis in CH2879 and JJ012 by GSK‐J4, but not in SW1353.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Thus, increased levels of d ‐2‐HG have been found in cartilage tumors with an IDH mutation, and are able to competitively inhibit α‐KG dependent histone demethylases, affecting trimethylation of the H3K27 as well as H3K4. However, no difference in levels of H3K27 and H3K4 trimethylation was observed between IDH mutant and IDH wildtype CSs. Additionally, previous studies and sequencing performed in the lab showed that CH2879 harbors IDH1/2 wild‐type, JJ012 IDH1‐mutant (p.Arg132Gly), and SW1353 IDH2‐mutant (p.Arg172Ser), while the current study show effective induction of apoptosis in CH2879 and JJ012 by GSK‐J4, but not in SW1353.…”
Section: Discussionmentioning
confidence: 97%
“…GSK‐J4 inhibits histone demethylases though interaction with α‐ketoglutarate (α‐KG)binding at active site of these histone demethylases. Consequently, IDH1 or IDH2 mutants, which have been found in more than half of CS samples, might affect GSK‐J4 sensibility in CS. Indeed, IDH1/2 mutants robustly modulate the status of α‐KG by catalyzing α‐KG to D‐2 hydroxyglutarate (D‐2HG), an antagonist of α‐KG.…”
Section: Discussionmentioning
confidence: 99%
“…IDH1 and IDH2 mutations do not correlate with grade of cartilaginous tumors: the mutations represent early events, and are retained through the life of the tumor, that is, as a tumor progresses from low to high grades and into a dedifferentiated phenotype, in local recurrences and in metastatic lesions. However, neither their presence, nor the different IDH1 mutations at residue p.R132, of which there are several, appear to impact on clinical outcome . This is in contrast with IDH1 mutations in glioblastomas which confer a better prognosis compared with IDH wild‐type brain tumors.…”
Section: Cartilaginous Tumorsmentioning
confidence: 93%
“…However, neither their presence, nor the different IDH1 mutations at residue p.R132, of which there are several, appear to impact on clinical outcome. 66,77 This is in contrast with IDH1 mutations in glioblastomas which confer a better prognosis compared with IDH wild-type brain tumors.…”
Section: Cartilaginous Tumorsmentioning
confidence: 96%
“…During the tricarboxylic acid cycle, IDH1/2 convert α‐ketoglutarate to d‐ 2‐hydroxyglutarate, an oncometabolite that inhibits TET enzymes and histone and DNA demethylases and thus indirectly alters the epigenome of chondrosarcomas . DNA and histone methylation changes are observed in chondrosarcomas but do not correlate on a broad scale with IDH1/2 mutations . These examples highlight the importance of studying epigenomic aspects of musculoskeletal cancers, even those that are characterized by recurrent genetic mutations because they could predict responders and non‐responders to therapies.…”
Section: Epigenetics and Orthopedic Oncologymentioning
confidence: 99%